2004
DOI: 10.1002/micr.20006
|View full text |Cite
|
Sign up to set email alerts
|

Concept of arteriovenous loupes in high‐risk free‐tissue transfer: history and clinical experiences

Abstract: The present study describes the concepts of arteriovenous (A-V) loupes prior to microsurgical free flap transfer in a selected high-risk group of patients. A one-stage concept was employed in 26 patients; 5 patients underwent two-stage flap transfer. Seven thrombotic occlusions of the A-V fistula or flap vessels were recorded; 6 patients underwent successful revision. Overall flap survival was 96.8% and compared favorably to reports in the literature. Defect coverage could be achieved in all but one case. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
0
20
0
2
Order By: Relevance
“…Traditional postoperative risk factors include venous congestion due to major trauma of the extremity (endothelial damage in arteries and/or veins), decreased movement and wound infection [12,13]. Kadota et al [14] showed in their study of 24 patients that postoperative (day 5 or later) wound infection was the most common (54%) cause of anastomotic thrombosis.…”
Section: Pathophysiology Of Anastomotic Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional postoperative risk factors include venous congestion due to major trauma of the extremity (endothelial damage in arteries and/or veins), decreased movement and wound infection [12,13]. Kadota et al [14] showed in their study of 24 patients that postoperative (day 5 or later) wound infection was the most common (54%) cause of anastomotic thrombosis.…”
Section: Pathophysiology Of Anastomotic Thrombosismentioning
confidence: 99%
“…Depending on the time and resources available, assessments can include imaging tests like thrombelastography (testing the efficiency of coagulation in blood) or Multiplate (bedside platelet analysis), which are becoming more routine. In order to minimize the risks of failure in high-risk patients, there is also the possibility of using vein interposition grafts or arteriovenous loops [12]. …”
Section: Principles Of Antithrombotic Therapy In Microvascular Surgerymentioning
confidence: 99%
“…6 On the other hand, the AV loop model is easier to establish, as it does not require vascular bundle sacrifice, and for this reason it has been successfully used even in difficult clinical conditions. 8 In principle, the ideal template for tissue regeneration should be a biocompatible and biodegradable scaffold, capable of ensuring optimal interaction with endothelial cells to promote angiogenesis, since the architecture of the scaffold and its biochemical characteristics are known to play a role in modulating the angiogenic activities of invading cells. 17 Among the engineered artificial dermis, the collagen-GAG template we used has proven to be a standard tool in reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]6,7 Moreover, the generation of microsurgical AV loops already has applications in the clinical field. 8 Here we revisit the microsurgical AV loop model and propose the utilization of a commercially available, crosslinked collagen-glycosaminoglycan (GAG) template (INTEGRA TM ) for the generation of highly vascular tissue engineering chambers. We show that collagen chambers that embed an AV loop, and are completely isolated from the surrounding tissue in a month-long period, are filled with newly formed soft connective tissue and become heavily vascularized.…”
mentioning
confidence: 99%
“…Cordeiro [10,11,12,18,44]. Zusätzlich kann auch die Verwendung von mikrochirurgisch anastomisierten AV-Loops die Einheilung von Transplantaten verbessern [5].…”
Section: Lappenkombinationen Und Mikrovaskuläre Technikenunclassified